Analysis of long-term survival in multiple myeloma after first-line autologous stem cell transplantation: impact of clinical risk factors and sustained response - Giesen, Nicola; Pritsch, Maria; Löpprich, Martin; Mai, Elias K.; Hillengaß, Jens; Goldschmidt, Hartmut; Raab, Marc-Steffen (Cancer medicine, 2018)
The widespread use of high‐dose therapy and autologous stem cell transplantation (ASCT) as well as the introduction of novel agents have significantly improved outcomes in multiple myeloma (MM) enabling long‐term survival. We here analyze factors influencing survival in 865 newly diagnosed MM patients who underwent first‐line ASCT at our center between 1993 and 2014. Relative survival and conditional survival were assessed to further characterize long‐term survivors. Achievement of complete response (CR) post‐ASCT was associated with prolonged progression‐free survival (PFS) in the whole cohort and with significantly superior overall survival (OS) in the subgroup of patients receiving novel agent‐based induction therapy. Landmark analyses performed at 1, 3, and 5 years post‐ASCT revealed that sustainment of any response had a highly significant influence on survival with no significant differences between sustained CR and sustained inferior responses. Furthermore, outcome was independently improved by administration of maintenance therapy. A subset of patients did experience long‐term survival >15 years. However, conditional survival demonstrated a persistent risk of myeloma‐associated death and cumulative relative survival curves did not show development of a clear plateau, even in prognostically advantageous groups. In conclusion, in this large retrospective study, sustained response after first‐line ASCT was found to be a major prognostic factor for OS independent of depth of sustained response. Administration of maintenance therapy further improved outcome, supporting the hypothesis that interventions to prolong responses achieved post‐ASCT may be essential to reach long‐term survival, especially in the setting of persisting residual disease.